TOL LANGIT UNTUK EKSPOR UMKM KERAJINAN SEBAGAI PENUNJANG EKONOMI KREATIF DENGAN PLATFORM AEXI.ID - Ita Athia; Astri Sukma Andini; Fitri Dwi Anggraeni (Universitas Islam Malang, 2022)
This community service activity was carried out by the KSM (Bachelor of Service Candidate) participant team at Unisma Malang. The target partners are aimed at the elite handy craft wood industry craftsmen in Pandansari village, Malang district, which experienced a 50% decrease in orders from usual. Service activities begin with observations and interviews of target partners to find out their strengths and weaknesses and measure the opportunities and challenges faced by partners. Then a SWOT analysis was carried out and the form of service activities was determined, namely by providing socialization and training on global marketing potential through the Aexi.id marketplace application for elite wood craftsmen and the Pandasari Village community. Before and after the training socialization activities, pre-test and post-test were conducted to measure the level of program success. The results obtained are that the craftsmen and participants are able to understand the material and apply the Aexi.id application directly and it is hoped that it can be applied in sustainable marketing activities to increase the marketing of the products of the elite handy craft wood creative industry during this pandemic..